Post-Pandemic Crisis Management: Grassroots Political Mobilization and Participation in Sigi - Ariana Yunus; Sunardi Sunardi; Haryanto Haryanto (Journal of Government and Civil Society, 2025)
This article aims to examine crisis management in the villages of Sigi Regency, Indonesia, with a focus on government policy interventions and grassroots mobilization in overcoming the post-COVID-19 crisis. This article uses a qualitative approach with a case study method, where data collection is carried out using interview and observation techniques. This article highlights the crisis management policy scheme in Sigi, which tends to be centralistic with more dominance by central government policies. However, grassroots social movements have emerged as an alternative to mitigating the post-pandemic crisis. We argue that the political participation of communities and voluntary movements has significant social resilience implications. Therefore, policy interventions involving grassroots communities have proven effective in crisis management. This study contributes to seeing citizen mobilization and participation as a form of alternative social resilience and offers insights into the importance of collaboration between government policy and community activism in dealing with crises in rural Indonesia.Â Artikel ini bertujuan mengkaji manajemen krisis di desa-desa kabupaten Sigi, Indonesia dengan fokus pada intervensi kebijakan pemerintah dan mobilisasi akar rumput dalam mengatasi krisis pasca COVID-19. Artikel ini menggunakan pendekatan kualitatif dengan metode studi kasus, dimana pengumpulan data dilakukan dengan teknik wawancara dan observasi. Artikel ini menyoroti skema kebijakan penanganan krisis di Sigi yang cenderung sentralistik dengan lebih banyak di dominasi oleh kebijakan pemerintah pusat. Namun, gerakan sosial dari akar rumput muncul sebagai alternatif dalam memitigasi krisis pasca pandemi. Kami berpendapat bahwa partisipasi politik komunitas dan gerakan sukarela memiliki implikasi ketahanan sosial yang signifikan. Oleh karena itu intervensi kebijakan yang melibatkan komunitas akar rumput terbukti efektif dalam manajemen krisis. Penelitian ini berkontribusi dalam melihat mobilisasi dan partisipasi warga sebagai bentuk ketahanan sosial alternatif dan menawarkan wawasan terkait pentingnya kolaborasi antara kebijakan pemerintah dan aktivisme komunitas dalam menghadapi krisis di pedesaan Indonesia.Â